A Contemporary Review on Friction Stir Welding of Circular Pipe Joints and the Influence of Fixtures on This Process - S. M. Senthil; M. Bhuvanesh Kumar; Milon Selvam Dennison (Advances in Materials Science and Engineering)
The permanent metal joining processes play a vital role in assembling the complex aluminium structures of the aerospace, automotive, marine, and oil industries. The invention of friction stir welding (FSW) redefined the mechanism of metal joining to produce high-quality welds by eliminating the consumption of electrodes and shielding gases, resulting in economical processes. Research works still lack to explore the application of FSW in complex geometries. In this view, the present work reports a critical review of various geometries welded by FSW, mainly circular geometries that are majorly used in the oil and gas industries. The various aspects of the FSW of pipes, such as process facilitation, process parameters, tool material selection, and tool design selection are discussed. The paper also presents insights into the parameters responsible for the weld quality, the feasibility of optimization techniques, and the status of various fixture arrangements. The facilitation requisites for FSW of pipes are also provided based on the reviews made. The review concludes by discussing the challenges associated with the FSW of pipes, economic aspects, and future research directions.